Mid‐Latitude Double H‐Spikes: Their Properties and Signatures in Different Geomagnetic Indices - E. Saiz; A. Guerrero; C. Cid (Space Weather)
Abstract Proper assessment of geomagnetic disturbances is a key aspect of space weather as technology is often impacted by space weather activity without previous warnings or proper forecasts. Double H‐spikes are a form of longitudinal asymmetry observed at midlatitudes. They are geomagnetic disturbances occurring simultaneously on the dayside and nightside as a negative/positive H‐spike, which go unnoticed through common geomagnetic indices. This work presents the results of a systematic search for double H‐spikes occurred over a 23‐year period and analyzes characteristics of the double H‐spikes such as the occurrence dependence on the solar cycle, season, intensity and phase of the geomagnetic storm. Our outcomes indicate that double H‐spikes are a global phenomenon closely related with the substorm phenomenon and the ground magnetic disturbances observed at mid‐latitude are remote effects of field‐aligned currents (FACs). FACs would be the part of the substorm current wedge developed from the expansion onset of intense substorms whose effects have wide longitudinal extend as they are observed on the dayside and the nightside. Also mid‐latitude global SYM and ASY indices are affected by FACs during those periods. Time derivatives of the SuperMAG SMR12 and SMR00 sector indices allow us to conclude that double H‐spikes, as short‐time high‐intensity magnetic disturbances, pose a potential risk to damage ground‐technological systems at midlatitudes.